2010
DOI: 10.1111/j.1445-2197.2010.05316.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant cholecystohepatic duct

Abstract: A 73-year-old lady presented with colicky central abdominal, anorexia, nausea and rigors. Physical examination revealed that she was afebrile, but had right upper quadrant tenderness, mildly deranged liver function and a white cell count of 25 ¥ 10 9 /L and a C reactive protein of 586 units. Abdominal ultrasound and computerised topography scanning findings were consistent with acute cholecystitis, (a large, thick walled gall bladder with pericholecystic fluid). She was initially treated with intravenous antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…In a study conduct on human fetuses, the incidence of ducts of Luschka was found to be 21.9%. In his recent review, Schnelldorfer 9 establishes a prevalence of SVBD from 4-10% in the general population. However, this data is probably underestimated because of the limited sensitivity of detecting these small ducts.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conduct on human fetuses, the incidence of ducts of Luschka was found to be 21.9%. In his recent review, Schnelldorfer 9 establishes a prevalence of SVBD from 4-10% in the general population. However, this data is probably underestimated because of the limited sensitivity of detecting these small ducts.…”
Section: Discussionmentioning
confidence: 99%